Artificial Intelligence (AI) in Educational Administration - Niyi Jacob Ogunode; Gregory, D. M (Research Parks Publishing LLC, 2023)
This paper examined application of Artificial Intelligence in educational administration and problems that may likely face the application of Al in educational administration in Nigeria. Using secondary data collected from both print and online publications the paper concluded that application of Artificial Intelligence in educational administration can lead to effective data analysis and decision making, effective school administrative, resource optimization, student support and intervention, streamlined communication and engagement and enhanced security and safety. The paper also identified bias and discrimination, lack of transparency and interpretability, data privacy and security breaches, problem of ethical and legal guidelines, inadequate technical expertise and resources, job displacement and lack of interoperability and compatibility, high cost of maintenance, power problem and unstable internet services as problems that may likely affected application of Artificial Intelligence in educational administration in Nigeria. Based on this problems identified, the paper recommended increment in investment to educational sector in Nigeria by the government.